Kedudukan Kompilasi Hukum Islam Dalam Tata Urutan Perundang-Undangan Di Indonesia - Helmi, Muhammad (Mazahib, 2016)
The Compilation of Islamic Law of Indonesia contains Islamic rules according to the conditions of Indonesian Muslims. The Compilation was formulated, among other things, by adopting an eclectic approach towards sunni schools of Islamic law (Madzahib al-Fiqh) and legal opinions (fatwa) of Indonesian Islamic scholars (ulama). It is now used by the judges in the religious courts as the substantive law in adjudicating Islamic family law cases: marriage, inheritance, and Islamic trust (waqf). Despite its deliberate drafting process, the Compilation is problematic to be a positive law in Indonesia especially after the enactment of Law No. 12 of 2011 concerning the establishment of statutes. This is because the Compilation was passed by means of the Presidential Instruction (or now decree) No. 1 of 1991. The format of Presidential Decree is not listed in the hierarchy of law in Indonesia either prior to or after the promulgation of Law No. 12 of 2011. This article aims to analyze the status of the Compilation as the positive law in Indonesia after the promulgation of Law No. 12 of 2011 and what measures can be taken by the government to elevate its status. It argues that the President can initiate to change the Compilation legal basis from Presidential Decree to Government Regulation in Lieu of Law. In following year, the Government Regulation in Lieu of Law can be passed as an Act. When it is an Act, the Compilation is officially effective and binding in Indonesia.